Access to coronary catheterisation: fair shares for all?. Issue 6915 (20th November 1993) - Kee, F; Gaffney, B; Currie, S; O'Reilly, D
Abstract : OBJECTIVE–To determine the effects of patient's sex and area's material deprivation on utilisation rates of coronary catheterisation and angiography in the investigation of ischaemic heart disease. DESIGN–Retrospective analysis of routinely collected hospital statistics. SETTING–Acute hospitals throughout Northern Ireland. SUBJECTS–24, 179 episodes of patients discharged from hospital with a primary diagnosis of ischaemic heart disease and 1270 episodes relating to patients with an underlying diagnosis of ischaemic heart disease who had either coronary catheterisation or angiography. MAIN OUTCOME MEASURES–Age standardised admission rates for heart disease and age standardised utilisation rates for catheterisation or angiography, or both, for 566 electoral wards ranked by Townsend "deprivation" scores. RESULTS–Catheterisation-angiography rates in men were over fivefold those of women, ranging from 85.5/100, 000 v 16/100, 000 in patients from "well off" areas to 123/100, 000 v 22/100, 000 for patients from deprived areas. After admission rates for heart disease were controlled for, the overall rate ratio for women was 0.48 (95% confidence interval 0.38 to 0.60). After differential admission rates for heart disease and other potential clinical confounders were controlled for, the investigation rates of patients from the least and most "deprived" areas were not significantly different (rate ratio 1.04 (0.87 to 1.25)). CONCLUSION–Although investigation rates were significantly lower in women than in men, further clinical data would be required before labelling this underutilisation as evidence of bias. There was no significant difference in invasive investigation rates for heart disease in areas of varying deprivation or affluence.